The Role of Sawung Dance Festival in Introducing Contemporary Dance to the Surabaya Community - Adela Sukma Ratnayu; Setyo Yanuartuti (Jurnal Seni Tari, 2025)
This study aims to determine and describe: the forms of activities held at the Sawung Dance Festival in an effort to introduce Contemporary dance. This study uses qualitative research methods. The data collection process includes observation techniques, documentation techniques, and interview techniques. The data validity technique used by researchers is triangulation techniques. In analyzing research data, researchers use three stages of data analysis, namely data reduction, data presentation and drawing conclusions / verification. The results of the study regarding the forms of activities held at the Sawung Dance Festival in an effort to introduce Contemporary dance are the registration of contemporary dance works then the selection and selection process of works, after the works are selected then the performance of the works. In addition to presenting selected works from contemporary choreography, the Sawung Dance Festival also displays the results of Sawung Dance production works. The Sawung Dance Festival also holds workshops for contemporary choreographers who want to develop the potential for creating contemporary dance works, of course with international standard speakers and trainers. The Sawung Dance Festival is presented at the Cak Durasim Building, East Java Cultural Park, Surabaya.